Electron Microscope Study of Ribonucleic Acid of Myxoviruses - Li, Kwok-Kwong (1971)
Intact ribonucleic acid (RNA) molecules in an extended form were extracted from purified influenza virus and observed in the electron microscope. For this study, the RNA extraction procedure and the Kleinschmidt protein monolayer technique were modified. The mean lengths of RNA from X7, X7-F1, and WSN strains of influenza virus were found to be 2.69, 2.55, and 2.37 μm, respectively. From these measurements, the corresponding estimated molecular weights would be 2.9, 2.8, and 2.5 × 10(6) daltons. X7 and WSN RNA preparations were exposed to pH 3 to disrupt intact molecules. Histograms of length measurements showed five peaks, which were interpreted to represent the five pieces of RNA reported to exist in the influenza virion. X7 RNA appeared to be more stable than WSN RNA when stored at 4 C. The profiles of histograms of incomplete virus RNA suggest that the high molecular-weight component is missing. In preliminary experiments on Newcastle disease virus RNA, molecules of various lengths were observed.